2010
DOI: 10.1007/s11069-010-9630-6
|View full text |Cite
|
Sign up to set email alerts
|

Space borne SAR observations of oceanic internal waves in North Bay of Bengal

Abstract: Sea surface manifestations of internal waves (IW) in the shallow continental shelf waters of North Bay of Bengal have been observed in almost all seasons imaged by Synthetic Aperture Radar (SAR) images of ERS1/2 and Envisat ASAR missions during the period 1993-2004. Shoreward propagating short-period IW packets are observed particularly in summer stratified coastal waters Off Chilka region. In summer waters, prominent short-period shoreward propagating internal waves of consecutive imageries of ERS-1/2 SAR (12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Some of these studies reported that internal tides in this region are mainly generated at the shelf breaks and on the continental slopes (Rao et al, ). Surface manifestations of shoreward propagating short period internal waves in the western BoB, particularly in the northern part of the coast (18–19°N), were also reported based on Synthetic Aperture Radar (SAR) imageries (Joshi et al, ; Prasad & Rajasekhar, ). Some previous studies noted strong internal tide generation near the head Bay and temporal variability in internal tide activity due to changes in stratification (Pradhan et al, ; Rao et al, ).…”
Section: Introductionmentioning
confidence: 70%
“…Some of these studies reported that internal tides in this region are mainly generated at the shelf breaks and on the continental slopes (Rao et al, ). Surface manifestations of shoreward propagating short period internal waves in the western BoB, particularly in the northern part of the coast (18–19°N), were also reported based on Synthetic Aperture Radar (SAR) imageries (Joshi et al, ; Prasad & Rajasekhar, ). Some previous studies noted strong internal tide generation near the head Bay and temporal variability in internal tide activity due to changes in stratification (Pradhan et al, ; Rao et al, ).…”
Section: Introductionmentioning
confidence: 70%
“…Although sole marks and the lower part of the classical tempestite beds can be easily explained with the unidirectional currents induced by breaking IWs (swash and backwash), the periclinalic dip orientation of laminae (bumped structure in the isotropic HCS) requires additional considerations. A relatively simple explanation would be to consider some interference such as reflection‐refraction between distinct trains of solitons or with sea‐bottom irregularities along the shelf such as canyons, banks, or islands (Prasad and Rajasekhar, 2011). Interference mechanism, or secondary internal waves (Vlasenko and Alpers, 2005) created by IWs approaching an obstacle on the sea floor, may also easily explain the tridimensional shape of isotropic HCS.…”
Section: Discussionmentioning
confidence: 99%
“…In the sharp density interface ( z = 29 m), the energy of zonal fluctuations averaged over a high‐frequency band (periods from ∼2 h to 9 min) is more than twice the energy of meridional fluctuations; the difference quickly ceased with depth, becoming 1 at z = 75 m, generally following the decrease of the total energy true〈ehftrue〉true(ztrue) shown in the left panel of Figure . Below 75 m, the ratio true〈Su/Svtrue〉 drops to 0.8 at z = 101 m, increasing then above 1.5 at z = 125 m. The true〈Su/Svtrue〉 ratio and quasiperiodic modulation of the internal wave energy suggest that the generation of high‐frequency oscillations in the upper part of the pycnocline may be linked to predominant zonal propagation of internal tide originated near the Andaman Islands [ Wijeratne et al ., ] or at the steep Sri Lankan continental slope [ Prasad and Rajasekhar , ] where the barotropic tides interact with bathymetry.…”
Section: Internal Wavesmentioning
confidence: 99%
“…Although satellite imagery shows the propagation of NLIW across the BoB toward Sri Lanka and their thronging along the continental shelf of India [ Jackson , ], NLIW to the west of Andaman and Nicobar Islands remains largely unexplored. Recently, NLIW observations from SAR images have been reported in the northern BoB [ Rao et al ., ; Prasad and Rajasekhar , ]. These waves propagated toward the Indian coast with wavelengths ∼600–700 m. On the Indian shelf of the northern BoB, semidiurnal tidal internal waves were characterized by amplitudes of ∼7 m, the amplitude of the diurnal internal tide being about half of it [ Sridevi et al ., ].…”
Section: Introductionmentioning
confidence: 99%